2020
DOI: 10.1115/1.4048351
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Sub-Grid Scale Modeling for Accurate Aerodynamic Simulations

Abstract: The Ahmed body is one of the most well-investigated vehicle bodies for aerodynamic purposes. Despite its simple geometry, the flow around the body, especially at the rear, is very complex as it is dominated by a large wake with strong interaction between vortical structures. In the present study, the flow around the 25° Ahmed body has been investigated using Large Eddy Simulations (LES) and compared to high-resolution particle image velocimetry (PIV) measurements. Special emphasis was put on studying three com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Recently Ekman et al [21] reported WRLES simulations of the Ahmed 25° car model at a Reynolds number of 𝑅𝑒 𝐻 = 0.26 • 10 6 . They used two hexahedral grids with 33.8 and 55.3 million cells and investigated three subgrid models.…”
Section: Introductionmentioning
confidence: 99%
“…Recently Ekman et al [21] reported WRLES simulations of the Ahmed 25° car model at a Reynolds number of 𝑅𝑒 𝐻 = 0.26 • 10 6 . They used two hexahedral grids with 33.8 and 55.3 million cells and investigated three subgrid models.…”
Section: Introductionmentioning
confidence: 99%
“…meteorology (Müller & Scherer 2005)) and engineering (e.g. aerodynamics (Ekman et al 2020)). The specific case of magnetized fluids comes with its own challenges, mostly related to the problem of the emergence of inverse cascades.…”
Section: Introductionmentioning
confidence: 99%